The Effect Of Paired Drill Training On The Ability Of Lower Passing Techniques In Volleyball Extracurricular Students Of SMP Negeri 20 South Bengkulu - Rostiana, Zizin; Retanza, Febra; Sumantri, Ajis (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of paired drill training on the ability of underhand passing techniques in volleyball extracurricular activities of students at SMP Negeri 20 Bengkulu Selatan. This study used a pre-experimental design method with the